Extracranial Internal Carotid Artery Tortuosity and Body Mass Index - Wang, Hai-Feng; Wang, Da-Ming; Wang, Jun-Jie; Wang, Li-Jun; Lu, Jun; Qi, Peng; Hu, Shen; Yang, Xi-Meng; Chen, Kun-Peng (Frontiers in Neurology, 2017)
Abstract: Background: Extracranial internal carotid artery tortuosity may trigger cerebral ischemia, and body mass index is a measure of body mass based on height and weight. The main purpose of this study is to determine the influence of body mass index on the tortuosity of extracranial internal carotid artery. Methods: A total of 926 carotid artery angiograms were performed in 513 patients, of which 116 cases and matched controls were selected. Arterial tortuosity was defined as simple tortuosity, kinking, or coiling. The severity of tortuosity was measured by tortuosity index, formula: [(actual length/straight-line length−1) ×100]. Results: Body mass indexes were different between the two groups (tortuosity: 27.06 kg/m2 (standard deviation 2.81kg/m2) versus none: 23.3kg/m2 (standard deviation 2.78kg/m2); p<0.001). Body mass index was independently and significantly associated with extracranial internal carotid artery tortuosity (OR 1.59; 95%CI, 1.35–1.86; P<0.001). Extracranial internal carotid artery tortuosity index is linearly associated with body mass index (exponential coefficient =1.067, p<0.001). The optimal predictive threshold of body mass index for extracranial internal carotid artery tortuosity was 25.47 kg/m2. The physiological mechanism underlying the reasons why higher body mass index has negative influence on extracranial carotid artery tortuosity may be an intra-abdominal hypertension caused by a much higher amount of body fat storied in visceral adipose tissue. Conclusion: Our result reveal a novel role for greater BMI on the presence of eICA tortuosity. For each increase in BMI of 1 kg/m2, there is a corresponding 1.59-fold increase in the risk of developing eICA tortuosity. The severity of extracranial internal carotid artery tortuosity increases linearly with increased body mass index.